Physiotherapists and patients with functional (psychogenic) motor symptoms: a survey of attitudes and interest. Issue 6 (11th April 2012) - Edwards, Mark J; Stone, Jon; Nielsen, Glenn
Abstract : Background: Functional (psychogenic) motor symptoms are commonly encountered in clinical neurology. Physiotherapy has face validity as a treatment for such symptoms and, anecdotally, referral of patients with functional motor symptoms (FMS) to physiotherapy services is common practice by neurologists. Here the authors sought to explore exposure to and attitudes towards patients with FMS among neurophysiotherapists. Method: The authors used an internet survey to gather information on the knowledge and attitudes of patients with FMS among 1402 members of a UK neurophysiotherapy organisation. Results: The response rate was 61%. Most physiotherapists saw patients with FMS, and for 25% of respondents these patients made up over 10% of their workload. Respondents were moderately interested in treating these patients (ranking them sixth out of 10 neurological conditions), but had low self-judged knowledge. Most respondents felt physiotherapy had more to offer patients with FMS, but felt poorly supported by referring neurologists and by inadequate service structures. Conclusions: Neurologists frequently refer patients with FMS to neurophysiotherapy services. Physiotherapists in general are interested in treating such patients and feel physiotherapy to be an appropriate treatment. However, inadequate service structures, knowledge and support from non-physiotherapy colleagues are judged to be barriers to provision of care.